Effects of high- and moderate-intensity training on metabolism and repeated sprints - Edge, J.; Bishop, D.; Goodman, C.; Dawson, B. (Medicine & Science in Sports & Exercise, 2005)
Purpose: We compared the effects of high-intensity interval (HIT) and moderate-intensity continuous (MIT) training (matched for total work) on changes in repeated-sprint ability (RSA) and muscle metabolism.